Sabah employers perception towards the implementation of minimum wage policy / Amirah Syazwani Ag Matasan and Siti Janariah binti Bacho - Ag Matasan, Amirah Syazwani; Bacho, Siti Janariah (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2013)
A study was conducted to know the perception of Sabah Employer towards the implementation of Minimum Wage Policy. The objectives of this research are to analyze the employer level of awareness on Minimum Wage Policy. Furthermore, this study also seeks the awareness on Minimum Wage Policy and measures its impact towards the employer acceptance. Lastly, this study also seeks to assess the employer positive perception towards the implementation on Minimum Wage Policy. A total of 100 respondents were selected as sample for the study using simple random sampling techniques. The study had been conducted in Kota Kinabalu area. A survey questionnaire was used for data collection